2009
DOI: 10.1590/s1517-86922009000600008
|View full text |Cite
|
Sign up to set email alerts
|

Taxa metabólica de repouso de ciclistas estimada por equações e obtida por calorimetria indireta

Abstract: A taxa metabólica de repouso (TMR) pode ser determinada por calorimetria indireta (CI). Porém, em função da praticidade, na prática clínica na maioria das vezes esta é estimada por equações de predição, as quais foram desenvolvidas em estudos envolvendo indivíduos não atletas. Apesar de alguns autores terem indicado que tais equações não estimam adequadamente a TMR, estas têm sido bastante utilizadas para calculá-la e prescrever dietas, inclusive para atletas. O objetivo deste estudo foi comparar a TMR determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Others, such as Watson et al, [37] used FFM in combination with anthropometric measurements, while Frings-Meuthen et al [38] and Reale et al [39] used it in combination with the fat mass. Methods of FFM measurement were different in these equations, that is, Dual-energy X-ray absorptiometry in the Cunningham equation [11] and Hannon et al, [31] air displacement plethysmography was used in the 10 Haaf et al, [19] and O'Neil et al [35] while BIA (InBody 720) was used in Kim et al, [25] BIA (Tanita) was used in Cocate et al [30] These methods encounter considerable variability in the measurement of FFM. Our research team's previous report showed that even different brands using the same technique of body composition analysis may have different FFM results, For example, Tanita versus InBody.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Others, such as Watson et al, [37] used FFM in combination with anthropometric measurements, while Frings-Meuthen et al [38] and Reale et al [39] used it in combination with the fat mass. Methods of FFM measurement were different in these equations, that is, Dual-energy X-ray absorptiometry in the Cunningham equation [11] and Hannon et al, [31] air displacement plethysmography was used in the 10 Haaf et al, [19] and O'Neil et al [35] while BIA (InBody 720) was used in Kim et al, [25] BIA (Tanita) was used in Cocate et al [30] These methods encounter considerable variability in the measurement of FFM. Our research team's previous report showed that even different brands using the same technique of body composition analysis may have different FFM results, For example, Tanita versus InBody.…”
Section: Discussionmentioning
confidence: 99%
“…This study included both genders and many sports, including group and individual games. The development of equations for a mixture of athletes playing different types of sports was seen in De Lorenzo et al, [ 17 ] 10 Haaf and Weijs, [ 19 ] Freire et al, [ 21 ] Jagim et al, [ 22 ] Frings-Meuthen et al, [ 38 ] and Reale et al [ 39 ] On the other hand, some equations were developed in 1 sport type or only 1 gender, such as (Cocate et al, [ 30 ] Hannon et al, [ 31 ] Joseph et al, [ 32 ] MacKenzie-Shalders et al, [ 33 ] Midorikawa et al, [ 34 ] O’Neil et al [ 35 ] ) creating a narrow limit for application in practice. The average TEE may differ in different sports based on the amount and duration of physical activity spent during the matches and the body mass of the player.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations